Detection and Functional Evaluation of the P2X7 Receptor in hiPSC Derived Neurons and Microglia-Like Cells - Francistiová, Linda; Vörös, Kinga; Lovász, Zsófia; Dinnyés, András; Kobolák, Julianna (Frontiers in Molecular Neuroscience, 2022)
A large body of evidence suggests the involvement of the ATP-gated purinergic receptor P2X7 (P2X7R) in neurodegenerative diseases, including Alzheimer’s disease. While it is well-described to be present and functional on microglia cells contributing to inflammatory responses, some reports suggest a neuronal expression of the receptor as well. Here, we present experimental results showing P2X7 receptors to be expressed on human hiPSC-derived microglia-like cells, hiPSC-derived neuronal progenitors and hiPSC-derived matured neuronal cells. By applying cell surface protein detection assays, we show that P2X7R is not localized on the cell membrane, despite being detected in neuronal cells and thus may not be available for directly mediating neurotoxicity. On hiPSC-derived microglia-like cells, a clear membranous expression was detected. Additionally, we have not observed differences in P2X7R functions between control and familial Alzheimer’s disease patient-derived neuronal cells. Functional assays employing a P2X7R antagonist JNJ 47965567 confirm these findings by showing P2X7R-dependent modulation of microglia-like cells viability upon treatment with P2X7R agonists ATP and BzATP, while the same effect was absent from neuronal cells. Since the majority of P2X7R research was done on rodent models, our work on human hiPSC-derived cells presents a valuable contribution to the field, extending the work on animal models to the human cellular system and toward clinical translation.